Las columnas impiden ver el bosque. - Sorela, Pedro (Estudios sobre el Mensaje Periodístico, 2000)
From the wide perspective of his own experience like press colunmist, novelist and professor of Journalims, the author reflects on the sense of the journalistic column genre, nowadays and in the future. He criticizes the press columnists pliable and self-complacent character. The author outlines his doubts about the columnist ability to understand the really interest core and to bring the light the newness, as required. Finally, he raises the most worrying issue: which is the originality of what is said?.